2013
DOI: 10.3892/or.2013.2345
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose dacarbazine-doxorubicin therapy against intra-abdominal desmoid tumors

Abstract: Abstract. Intra-abdominal desmoid tumor is a lifethreatening disease. Studies have shown that dacarbazine (DTIC)-doxorubicin (DOX) (D-D) therapy is the most effective treatment. However, myelosuppression is a major problem, and cardiac muscle disorders due to DOX limit the number of administration cycles, whereas it usually requires a long time to achieve tumor shrinkage. To resolve these issues, we introduced low-dose D-D therapy to 3 patients employing 50 mg/m 2 DOX and 600-700 mg/m 2 DTIC per cycle, which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Neurotoxicity of NVB is less than that of VBL, and the therapeutic effect is the same (31). MTX+VBL therapy was used in 27 cases in Garbay's study (23). The median chemotherapy duration lasted for 18 weeks, 4 patients achieved PR (15%), 14 achieved SD (52%), and 9 suffered PD (33%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotoxicity of NVB is less than that of VBL, and the therapeutic effect is the same (31). MTX+VBL therapy was used in 27 cases in Garbay's study (23). The median chemotherapy duration lasted for 18 weeks, 4 patients achieved PR (15%), 14 achieved SD (52%), and 9 suffered PD (33%).…”
Section: Discussionmentioning
confidence: 99%
“…All of the patients had remission. In Garbay's study (23), combined chemotherapy was delivered in 44 (71%) cases, monotherapy in 18 (29%) patients, and 13 (21%) patients received an anthracyclinecontaining regimen. The most common nonanthracycline regimen was MTX-VBL combination (n=27).…”
Section: Traditional Pharmacotherapymentioning
confidence: 99%
“…It has been reported that cytotoxic-chemotherapy benefits about 20 to 75 % of treated desmoid patients [ 19 ]. Several studies indicated the efficacy and safety of the chemotherapy regimen of doxorubicin and dacarbazine combination in treating patients with Gardner’s syndrome-associated desmoid tumors [ 8 , 9 , 20 , 21 ]. Gega combined DOX, DTIC, and meloxicam in the treatment of Gardner’s syndrome-associated desmoids and achieved a great success with high rates of partial or complete response [ 8 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Alternatively, we speculate that reduction of the dosage may eliminate the adverse effect of DOX-DTIC-meloxicam. In fact, Yamaoto employed low-dose DOX-DTIC therapy to three patients against intra-abdominal desmoids, which was a safe and effective regimen and permitted repeated administration cycles (50 mg/m 2 DOX and 600–700 mg/m 2 DTIC per cycle) up to 10–11 times [ 21 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…The poor results obtained by surgery on the treatment of relapse, also because of the hyperplasiogenous stimulus that such treatment determines, have made this approach a secondary choice or at least one which follows complementary treatments such as radiation therapy, which seems to achieve a control of tumor growth in 40 to 80% of cases [ 4 , 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%